Implementación de un sistema de inteligencia de negocios en el departamento de ventas del Almacén Deportivo CTL SPORTS mediante la aplicación de herramientas BI para un adecuado proceso de toma de decisiones gerenciales. - Álvarez Ibarra, Maria Liseth (2022)
Business intelligence is defined as a discipline that helps companies to make decisions based on the analysis of historical information of their processes, therefore, it is a worldwide technological trend that allows any type of company to have information quickly and efficiently. In the Company CTL SPORTS, since the arrival of the pandemic, its sales have stagnated and it has not been posible to determine alternatives to this problema. The above is used as a basis for our objective to implement a business intelligence system in the sales department of the company CTL SPORTS through the application of business intelligence tools for an adequate management decision-making process. To fulfill the objective, we applied bibliographic research that allowed us to understand scientific database publications that provided the precise theoretical foundations. Subsequently, we conducted exploratory and field research that allowed us to know the limited information to which the management has access and the necessary requirements of the company. As a result, we selected some tools such as HTML, bootstrap, jquery, and PHP for the development of a business intelligence system based on an MVC architecture (Model, View, Controller), which in conjunction with Microsoft Power Bi and the Kimball methodology allowed the deployment of interactive reports from a MySql database. Finally, we can conclude that the effective implementation of a business intelligence system under an appropriate methodology helps to provide cutting-edge technological solutions in the different areas or processes of the companies for adequate management decision-making.